Construction characteristics and reinforcement and maintenance technology of native earth buildings in Liling area - Yujia Fan; Chao Wang; Haiting Sun; Jun Mu (Journal of Asian Architecture and Building Engineering)
Traditional earth dwellings in Weishan Village, Liling City, Hunan Province, China, have experienced hundreds of years of wind and rain. In order to asses their seismic performance, a field survey was conducted on representative traditional rammed earth buildings in Liling Kiln area of Weishan Village. The research uses a variety of methods, including on-site investigation, 3D laser scanner tilt analysis, deformation chromatography analysis, wood material detection, and stress wave analysis, to obtain the main structural forms and material characteristics of local earth buildings. The main structural problems of rammed earth buildings were summarized through the investigation: the foundation and roof were no longer stable, the problems of sag, tilt and cracking were common in rammed earth walls, and the wood parts were gradually rotting and splitting. According to the investigation results, the seismic measures to improve rammed earth buildings were proposed from different parts of the damaged houses, in order to provide guidance for the local villagers’ residential construction, house reinforcement and renovation design.